Improvement of scientific and methodological approaches to the classification of agricultural lands - Dorosh, Y.; Barvinskyi, A.; Dorosh О.; Saliuta, V. (Land Management, Cadastre and Land Monitoring, 2021)
The existing scientific and methodological approaches to the classification of agricultural lands both in Ukraine and abroad are analysed. It is established that modern classifications of lands should be formed based on such principles as complexity, exhaustiveness, hierarchy and legality; meet the requirements of automated technologies for maintaining the state land cadastre and land monitoring; take into account the recommendations of the European Economic Commission at the UN. Comprehensiveness of identifying of all potentially possible land uses, which will facilitate effective state control over land use in accordance with their intended purpose will be ensured through a comprehensive approach to the development of land classification; its consistency with other current state classification systems in the field of nature management and the use of clearly defined target criteria, parameters and features, the system of which is determined by the specific scope and requirements of the relevant user groups – through a systematic approach. A fragment of 3-digit classification of agricultural lands is proposed, in which hierarchically placed interrelated indicators characterizing the legal regime of land use (legal block of land classifier) and their physical condition (physical block of land classifier) are placed hierarchically. In order to legally consolidate the categories “type, subtype, variety of lands” that form the basis of the physical block of the land classifier, it is necessary to make appropriate changes to the national land legislation. Key words: agricultural lands, land classification, land category, intended purpose.